2015
DOI: 10.1016/j.bbmt.2015.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Transplant Outcomes for Children with T Cell Acute Lymphoblastic Leukemia in Second Remission: A Report from the Center for International Blood and Marrow Transplant Research

Abstract: Survival for children with relapsed T-ALL is poor when treated with chemotherapy alone and outcomes after allogeneic hematopoietic cell transplantation (HCT) is not well described. Two hundred and twenty-nine children with T-ALL in second complete remission (CR2) received a HCT following myeloablative conditioning between 2000–2011 and were reported to the Center for International Blood and Marrow Transplant Research (CIBMTR). Median age was 10 (range, 2–18) years. Donor source was umbilical cord blood (26%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…We observed that disease risk at diagnosis (including high leukocyte count and adverse cytogenetics) did not influence the outcomes of ALL patients receiving haplo‐HSCT . Other studies also reported that leukocyte count did not influence the outcomes of ALL children after UCBT . These suggested that both haplo‐HSCT and UCBT could overcome the poor prognostic significance of risk factors at diagnosis of ALL children receiving transplantation.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…We observed that disease risk at diagnosis (including high leukocyte count and adverse cytogenetics) did not influence the outcomes of ALL patients receiving haplo‐HSCT . Other studies also reported that leukocyte count did not influence the outcomes of ALL children after UCBT . These suggested that both haplo‐HSCT and UCBT could overcome the poor prognostic significance of risk factors at diagnosis of ALL children receiving transplantation.…”
Section: Discussionmentioning
confidence: 52%
“…30 Other studies also reported that leukocyte count did not influence the outcomes of ALL children after UCBT. 38,39 These suggested that both haplo-HSCT and UCBT could overcome the poor prognostic significance of risk factors at diagnosis of ALL children receiving transplantation. Although Gonz alez-Vicent et al 10 observed that age at transplantation was one of the main prognostic factors of DFS, several older adolescents ( 15 years old) were included in their study, and other studies have not observed an influence of age in children receiving UCBT or haplo-HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by the Center for International Blood and Marrow Transplant Research showed the 3-year overall survival (OS) with HSCT is 48% for patients able to achieve complete second remission (CR2) prior to transplantation. 41 For patients with first relapse of T-ALL/LLy, achieving CR2 is the most important step prior to HSCT, as disease status at the time of transplantation remains the most important factor associated with overall survival. 42 However, attaining clinical remission after relapse remains the biggest therapeutic challenge in T-cell disease, and most patients are unable to receive transplantation given the aggressive nature of relapsed disease.…”
Section: Discussionmentioning
confidence: 99%
“…Published reports have described comparable outcomes for recipients of grafts from matched sibling donors (MSDs) and unrelated matched donors (UMDs), with an EFS of 60% to 70% [6][7][8]. Outcomes after alternate donor transplantations with either haploidentical or cord blood transplants are generally reported as less favorable, largely related to higher treatment-related mortality (TRM) [9][10][11], but most published studies did not directly compare these alternative donor transplants with MSD and UMD transplants.…”
Section: Introductionmentioning
confidence: 99%